Opening the curiosity box : botanical images as sites of transformation for the scientific practices of annotation and display in the seventeenth and eighteenth centuries - Stewart, Karen (Stellenbosch : Stellenbosch University, 2012)
Thesis (MPhil) -- University of Stellenbosch, 2007.